Correlating Laboratory Conditioning with Field Aging for Asphalt using Rheological Parameters. Issue 5 (May 2020) - Zhang, Runhua; Sias, Jo E.; Dave, Eshan V.
Aging has a significant effect on performance of asphalt materials. Reliable characterization of asphalt binder properties with aging is crucial to improving asphalt binder specifications as well as modification and formulation methods. The objective of this study is to correlate the laboratory conditioning methods with field aging using evolution of binder rheological parameters with time and pavement depth. Loose mixtures are aged in the lab (5 and 12 days aging at 95°C, and 24 h at 135°C) and recovered binder rheological properties are compared with those from different layers of field cores. The virgin binder results with 20 h pressure aging vessel (PAV) aging are also included. Binder testing is conducted using a dynamic shear rheometer with a 4 mm plate over a wide range of frequencies and temperatures. Rheological parameters calculated from the master curves, performance grade system, and binder Christensen–Anderson–Marasteanu model are used to evaluate changes with aging. The field aging gradient is evaluated, and the laboratory conditioning durations corresponding with the field aging durations at different pavement depths are calculated. The results show that 5 days of aging can simulate around 8 years of field aging (in New Hampshire) for the top 12.5 mm pavement, and 12 days' aging can simulate approximately 20 years; 20 h PAV binder aging is not adequate to capture the long-term performance of the pavement. This study provides a way to optimize the laboratory conditioning durations and evaluate the performance of asphalt material with respect to pavement life (time) and depth (location) within the pavement structure.